Halo vest immobilization – an institutional review of safety in acute cervical spine injury from 2013 to 2017. (3rd September 2021) - Malnik, Samuel L.; Scott, Kyle W.; Kuhn, M. Zino; Alcindor, Dunbar; Tavanaiepour, Kourosh; Tavanaiepour, Daryoush; Crandall, Marie; Rahmathulla, Gazanfar
Abstract: Objective: Halo vest immobilization (HVI) remains an important treatment option for occipital-cervical injuries. It provides the surgeon with a safe and effective medical treatment options for challenging patients. The aim of this study was to evaluate the safety of HVI in these patients. Methods: This retrospective study identified adult patients treated with Halo vests immobilization (HVI) for acute cervical spine injury at our metropolitan level 1 trauma center from 2013 to 2017. This heterogenous cohort included 67 consecutive patients with acute cervical spine injury secondary to trauma or iatrogenic injury following surgical intervention with a mean age of 52 and a mean injury severity score (ISS) of 18. Forty-six percent of patients were treated with HVI as an adjunct therapy to surgical fixation (both short- and long-term immobilization), 45% of patients were treated with HVI as a primary medical treatment, and 9% of patients were treated with HVI instead of failed conservative medical treatment, such as cervical braces. Results: Pneumonia during the initial hospital stay was the most common complication (25%), followed by the correction of loose pins (22%) and pin site infections (18%). Overall, 51% of patients experienced at least one of these complications. There were significant associations between low initial GCS scores and the development of pneumonia (p < 0.001), high ISS scores and the development of pneumonia (p < 0.01), and duration of HVI and the occurrence of loose pins (p < 0.05). Four patients initially treated with HVI as primary medical treatment was converted to surgical treatment due to an intolerance of HVI or non-healing injuries. Conclusions: The HVI is a safe and effective treatment modality in a subset of patients with complex cervical junction and subaxial cervical spine pathology.